Intranasal administration of erythropoietin rescues the photoreceptors in degenerative retina: a noninvasive method to deliver drugs to the eye - Ye Tao; Chong Li; Anhui Yao; Yingxin Qu; Limin Qin; Zuojun Xiong; Jianbin Zhang; Weiwen Wang (Taylor & Francis Group, 2019)
Inherited retinopathies typically lead to photoreceptor loss and severe visual impairments in the subjects. Intranasal administration is an efficient approach to deliver therapeutic agents to the targeted tissue. The present study is designed to deliver the erythropoietin (EPO) into the N-methyl-N-nitrosourea (MNU) induced mice, a pharmacological retinopathy model via intranasal or intravenous route. The mice were then subjected to bioavailability assay and therapeutic effects evaluation. Our results showed that the intranasal delivery of EPO is effective to alleviate the morphological disruptions in the MNU induced mice. The intranasal delivery of EPO also ameliorated the visual impairments in the MNU induced mice. Immunostaining experiment showed that both the M-cone and S-cone populations in the degenerative retinas are rescued by the intranasal delivery of EPO. In particular, the M-cone photoreceptors in dorsal-temporal (DT) quadrant and the S-cone photoreceptors in ventral-nasal (VN) quadrant were preferentially preserved by the intranasal delivery of EPO. Mechanism studies showed that the intranasal delivery of EPO could the modulate apoptosis and restrict oxidation in the degenerative retina. Compared with intravenous delivery, the intranasal delivery led to the significantly higher EPO concentration in the retina. The intranasal delivery resulted in more potent protection and had less erythropoiesis-stimulating activity than the intravenous delivery. Our results suggest that the intranasal administration is a noninvasive and efficient approach to deliver EPO into the retinas. These findings lay the groundwork for further intranasal administration of EPO in ophthalmological practice.